2017
DOI: 10.3324/haematol.2017.170118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior therapy on the efficacy and safety of oral ixazomib-lenalidomide-dexamethasone vs . placebo-lenalidomide-dexamethasone in patients with relapsed/refractory multiple myeloma in TOURMALINE-MM1

Abstract: Prior treatment exposure in patients with relapsed/refractory multiple myeloma may affect outcomes with subsequent therapies. We analyzed efficacy and safety according to prior treatment in the phase 3 TOURMALINE-MM1 study of ixazomib-lenalidomide-dexamethasone (ixazomib-Rd) versus placebo-Rd. Patients with relapsed/refractory multiple myeloma received ixazomib-Rd or placebo-Rd. Efficacy and safety were evaluated in subgroups defined according to type (proteasome inhibitor [PI] and immunomodulatory drug) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 25 publications
(31 reference statements)
2
25
1
1
Order By: Relevance
“…In this analysis, patients in most prespeci ed subgroups reported an improved PFS in the IRD cohort when compared to patients in the RD cohort; unlike the TOURMALINE-MM1 trial, we did not observe worse outcomes of the IRD regimen in patients undergoing ASCT. 7 However, this analysis showed that patients with higher pretreatment received less bene t from IRD than patients treated in early relapses. In addition, patients with the presence of extramedullary plasmocytoma had signi cantly worse outcomes that were comparable in the IRD arm than in the RD cohort (median PFS 5.5 vs 11.2 months).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this analysis, patients in most prespeci ed subgroups reported an improved PFS in the IRD cohort when compared to patients in the RD cohort; unlike the TOURMALINE-MM1 trial, we did not observe worse outcomes of the IRD regimen in patients undergoing ASCT. 7 However, this analysis showed that patients with higher pretreatment received less bene t from IRD than patients treated in early relapses. In addition, patients with the presence of extramedullary plasmocytoma had signi cantly worse outcomes that were comparable in the IRD arm than in the RD cohort (median PFS 5.5 vs 11.2 months).…”
Section: Discussionmentioning
confidence: 85%
“…The novel triplet IRD (ixazomib, lenalidomide, dexamethasone) has been approved in more than 70 countries for patients with relapsed and refractory multiple myeloma (RRMM) based on the results of several clinical trials including TOURMALINE-MM1 (NCT01564537). [1][2][3][4][5][6][7][8] The results of clinical trials, however, are usually not representative of the typical "real-world" patient in the community setting; the population recruited to these studies is subject to signi cant selection bias which utilizes inclusion and exclusion criteria to predominantly enroll less pre-treated and healthier patients, usually with better overall life expectancy. 9,10 This prospectivaly de ned analysis of the Czech Registry of Monoclonal Gammopathies (RMG) will present real-world clinical outcomes for patients with RRMM treated in routine clinical practice in the Czech Republic.…”
Section: Introductionmentioning
confidence: 99%
“…Although patients refractory to PIs or lenalidomide were excluded from TOURMALINE-MM1, the results of this trial demonstrated that PFS significantly improved by adding ixazomib to lenalidomide and dexamethasone in patients with 1 prior therapy without transplant (HR 0.60), and 2 or 3 previous lines of treatment (HR 0.58), regardless of previous exposure to PI or IMIDs. This benefit was reported also in patients refractory to their last therapy (HR 0.71)[47,48].Easy oral administration, good safety/efficacy profile, and the need for newer therapeutic strategies to face MM intrinsic chemoresistance and genetic instability, provide the rationale to implement and evaluate ixazomib in novel agent-combinations, such as with thalidomide, pomalidomide[49], panobinostat, selinexor, daratumumab, and also in association with conventional, more economically sustainable chemotherapeutic drugs, such as cyclophosphamide, and melphalan . [50-To be appropriate for LTTs, a drug should be effective, safe, easy-to-take and, possibly, not excessively expensive.…”
mentioning
confidence: 54%
“…Results from this study demonstrated a significant progression‐free survival (PFS) benefit in the intent‐to‐treat (ITT) analysis. A subgroup analysis showed that while IRd was associated with clinical benefit compared with placebo‐Rd, the greatest benefit was observed in patients who had received 2 or 3 prior lines of therapy (LoT; 2/3LoT patients) compared to patients who had received 1 prior LoT (1LoT patients) . We therefore conducted analyses of RNA sequencing (RNAseq) data from tumors collected during TOURMALINE‐MM1 and investigated the molecular differences between tumors from patients according to number and/or type of prior therapies.…”
Section: Introductionmentioning
confidence: 99%